Portrait of Communication and Sea Sand Mining Conflict in Indonesia - Muldi, Ail; Nurjuman, Husnan; Framani, Naniek Afrilla; Saryani, Yayan (Komunitas: International Journal of Indonesian Society and Culture, 2024)
Conflicts over sea sand mining in Indonesia has intensified over the past ten years as more concessions have been granted to companies engaged in sea sand production. The location of the sea sand mine overlapping with fishermen's fishing grounds and the lack of communication cause conflicts between coastal and small islands society and local governments, as well as companies that hold license or companies that conduct sea sand mining. The sea sand mining conflicts in three provinces has occurred, escalated and reached the stage of violence. The research used a variety of conflict analysis tools to explain the typology, stages, cycles and applicable conflict management. The research used qualitative methods with a multi-special approach and data collection was carried out by interviewing several informants, and researching documentation studies including literature from similar previous research documentation. The research found that the resolution of sea sand mining conflicts that occurred on the islands of Sumatra, Sulawesi and Nusa Tenggara was competitive with a lose-win orientation. Conflict settlement took place with one party conceding to the other, third-party intervention and consideration on the demand of sea sand market. In three research locations it is known that conflict resolution fails to address the root cause of the issue, causing it to revert to the basic stage of conflict. As a result, at some point, conflict can escalate and become apparent as in line with market demand after the legalization of sea sand exports.